Surface water availability of the Suaçuí river basin: analysis by different methodologies for defining the reference flow rate (Research, Society and Development, 2022)
For the analysis of water availability in a hydrographic basin the knowledge of the reference flow rate becomes indispensable. In the state of Minas Gerais the flow rate Q7,10, is used, in which a portion of this reference flow rate is granted, which can be defined by different methodologies. In this sense, this study aims to analyze the surface water availability of the Suaçuí river basin (MG) using three methodologies to define the reference flow rate: statistical analysis of historical flow series in the fluviometric stations; Surface water runoff in the state of Minas Gerais; and Flow regionalization study to improve the allocation process in the state of Minas Gerais. Considerable variations between the methods used were verified, with intervals of -19.94% to 1304.6% comparing the two flow regionalization methods used, in relation to the analysis of the data from the fluviometric stations. By the different methods, the water levels captured in the respective sub-basins do not produce impacts capable of compromising water availability, except for the area upstream of the "Fazenda Corrente" station, where the results indicate a certain degree of compromising water availability. Future research that compares other methods of flow regionalization is recommended, seeking results with smaller statistical variations in relation to the observed fluviometric stations, or even the development of specific methods for the studied watershed, in order to contribute to the decision-making process in the management of water resources.